2023
DOI: 10.1183/13993003.01763-2022
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and asthma and COPD in adulthood: a nationwide register study from two Nordic countries

Abstract: Preterm birth affects lungs in several ways but only few studies have follow-up until adulthood. We investigated the association of the entire spectrum of gestational ages with specialist care episodes for obstructive airway disease (asthma and chronic obstructive pulmonary disease, COPD) at age 18–50 years. We used nationwide register data on 706 717 people born 1987–1998 in Finland (4.8% preterm) and 1 669 528 born 1967–1999 in Norway (5.0% preterm). Care episodes of asthma and COPD were obtained from specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In our study, prematurity was positively related to the future development of asthma and AR in the pediatric population, while being protective against the development of AD. These results are consistent with ndings from other nationwide databases or reviews on asthma and AD, with a stronger correlation observed as gestational age decreases 6, [15][16][17] . Although beyond the scope of this study, the possible etiology of prematurity-associated asthma is multifactorial.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, prematurity was positively related to the future development of asthma and AR in the pediatric population, while being protective against the development of AD. These results are consistent with ndings from other nationwide databases or reviews on asthma and AD, with a stronger correlation observed as gestational age decreases 6, [15][16][17] . Although beyond the scope of this study, the possible etiology of prematurity-associated asthma is multifactorial.…”
Section: Discussionsupporting
confidence: 91%
“…The link between preterm birth and long-term risk of respiratory infections, particularly lung infections, seems plausible because preterm birth is strongly associated with lung immaturity and the need of ventilatory support in the neonatal period. 33 For preterm born, lower lung volumes and higher rates of chronic lung disease have been reported through childhood and into adulthood, 33 , 34 , 35 , 36 , 37 , 38 and associations between preterm birth and RTI risk in childhood and adolescence have been described previously. 25 , 28 , 34 , 36 Reduced respiratory organ function and chronic lung disease increase the risk of RTIs in children as well as in adults, and an increased risk of chronic lung disease (CLD) in childhood and adulthood may, at least in part, mediate the excess RTI risk in children and adults born preterm.…”
Section: Discussionmentioning
confidence: 76%
“… 25 , 28 , 34 , 36 Reduced respiratory organ function and chronic lung disease increase the risk of RTIs in children as well as in adults, and an increased risk of chronic lung disease (CLD) in childhood and adulthood may, at least in part, mediate the excess RTI risk in children and adults born preterm. 38 However, the increased risk of RTI and CLD in children born preterm are likely intertangled and cannot be solely explained by structural changes in the lung. Although the precise mechanisms are not yet fully understood, it is likely that the development of lung disease in early life is also connected to the establishment of the microbiota and the maturation of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…R. Faner Canet (Barcelona, Spain) discussed the importance of gene–environment interactions in the pathogenesis of COPD. Being born severely preterm (<28 weeks gestational age) is associated with a 7-fold increased risk of developing COPD by age 30–50 years [ 32 ]. This links to another study of preterm children who underwent COPD polygenic risk scoring.…”
Section: Scientific Year In Reviewmentioning
confidence: 99%